2019
DOI: 10.3390/ijerph16142449
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Effects of Forest Therapy on Sleep Quality in Patients with Gastrointestinal Tract Cancers

Abstract: The improvement of sleep quality in patients with cancer has a positive therapeutic effect on them. However, there are no specific treatment guidelines for treating sleep disturbance in cancer patients. We investigated the effect of forest therapy on the quality of sleep in patients with cancer. This study was conducted on nine patients (one male, eight female; mean age, 53.6 ± 5.8 years) with gastrointestinal tract cancer. All patients participated in forest therapy for six days. They underwent polysomnograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…Forest therapy for insomnia, which can induce a decrease in the secretion of cortisol, might be one of the ways to break this vicious cycle. In 2018, the effectiveness of a forest therapy program for patients diagnosed with cancer was verified through a preliminary study, which showed increased sleep efficiency and sleep initiation times through polysomnographic findings [ 4 ]. After reviewing previous studies about forest therapy and nonpharmacological treatments for insomnia and menopause, various activities for relaxing and meditating in the forest are expected to have synergistic effects in insomnia and menopause treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forest therapy for insomnia, which can induce a decrease in the secretion of cortisol, might be one of the ways to break this vicious cycle. In 2018, the effectiveness of a forest therapy program for patients diagnosed with cancer was verified through a preliminary study, which showed increased sleep efficiency and sleep initiation times through polysomnographic findings [ 4 ]. After reviewing previous studies about forest therapy and nonpharmacological treatments for insomnia and menopause, various activities for relaxing and meditating in the forest are expected to have synergistic effects in insomnia and menopause treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, there is no study detailing how long staying in a forest is effective or not. Through the experience of our prior research, participants were unable to sleep on the first day of the program due to unfamiliar sleeping environments [ 4 ]. Based on several previous trials of forest therapy, our program’s duration was set at five nights and six days [ 1 , 2 , 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest therapy is a health promotion method that is based on the forest environment and activities such as walking and rest. Forest therapy has been proven to have a favorable influence on the health of the human body and mind in many medical studies [40,41,42,43,44,45,46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the online platforms of mHealth [33] and cognitive behavioural therapy for insomnia (CBTi) [34] are resourceful, easily accessible materials for shift workers. Forest therapy (originating in the 1980s in Japan for stress reduction) that improved sleep efficiency in cancer patients [35] may be explored in shift workers in future studies.…”
mentioning
confidence: 99%